2020
DOI: 10.1111/liv.14606
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B surface antigen, core‐related antigen and HBV RNA: Predicting clinical relapse after NA therapy discontinuation

Abstract: Background & Aims The safe discontinuation of nucleos(t)ide analogue therapy remains challenging in chronic hepatitis B. We investigated the potential role of quantitative hepatitis B surface antigen, hepatitis B core‐related antigen and hepatitis B virus RNA at the end of treatment in predicting off‐therapy relapse. Methods Patients who fulfilled the stopping criteria of the Asian Pacific Association for the Study of the Liver guideline were enrolled. Virological relapse was defined as hepatitis B virus DNA l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
66
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(73 citation statements)
references
References 30 publications
(41 reference statements)
4
66
1
Order By: Relevance
“…Close monitoring every 3 months and prompt initiation of NUCs may be more cost-effective. In the future with more solid evidence, new biomarkers, such as HBV RNA, HBcrAg, may be helpful to decide when to terminate NUCs after completion of IST [ 103 ].…”
Section: Methodsmentioning
confidence: 99%
“…Close monitoring every 3 months and prompt initiation of NUCs may be more cost-effective. In the future with more solid evidence, new biomarkers, such as HBV RNA, HBcrAg, may be helpful to decide when to terminate NUCs after completion of IST [ 103 ].…”
Section: Methodsmentioning
confidence: 99%
“…Virological and CR rates in patients with detectable EOT HBcrAg were 53.0–74.1%, and 39.5–48.3%, respectively, compared with 14.0–44.1% and 7.3–13.9%, respectively, in patients with undetectable HBcrAg 20,22,25,26,36 . Cut‐off values for EOT HBcrAg in these studies ranged from undetectable (<2 or 3 log 10 IU/mL) to 4.5 log 10 IU/mL with area under the receiver operating characteristic curve (AUROC) of 0.69–0.70 for predicting VR and 0.61–0.77 for predicting CR 18,20,22,26,30,38 . Because HBeAg status might affect the predictive value of HBcrAg, we divided the studies according to HBeAg status.…”
Section: Resultsmentioning
confidence: 86%
“…As shown in Table 2, stopping rules varied among studies. These rules include (i) stopping at physician's discretion in three studies, 31,34,37 (ii) adopting Asian‐Pacific Association for Study of the Liver guidelines in three studies, 22,26,32 (iii) after achieving virological remission on NA therapy in seven studies, 20,21,24,25,28–30 (iv) after achieving biochemical remission in one study, 18 and (v) after achieving both virological and biochemical remission in two studies 23,36 . All studies that enrolled HBeAg‐positive CHB patients required HBeAg seroconversion prior to the cessation of NA therapy.…”
Section: Resultsmentioning
confidence: 99%
“…A recent report indicated that no clinical relapse occurred after cessation of NAs therapy among HBeAg-positive and HBeAg-negative patients with undetectable HBV RNA and HBcrAg at EOT. 29 It would be interesting to investigated whether the combination of HBcrAg with HBV RNA could further reduce the risk of HBV relapse in HBeAg-negative patients who discontinued entecavir treatment.…”
Section: Discussionmentioning
confidence: 99%